(untitled) (AYUSHDHARA, 2017)
Diabetes mellitus is globally one of the threatening disease which is creating a havoc worldwide. The oral hypoglycaemic drugs in many patients do not produce desired effects and those who respond, gradually lead to the therapeutic failure in the later stages of the disease. So, in the present situation to overcome this problem it is highly needed to break through an alternative therapy. In view of the above fact the present study was undertaken, whereby the drug taken was Amrita-Shilajit yoga, as a combination drug having Rasayana properties and the subjective parameters taken for assessing was Agni and Ojas, along with objective, laboratory parameters like Fasting Blood sugar and Post prandial sugar for evaluating the benefits of the drug in Diabetes Mellitus. Three groups were taken (n=30, 10 for each group). Group A, receiving Amrita Shilajatu yoga, Group B receiving modern drug and Group C receiving both the drug. In case of group A mean reduction of all the clinical parameters are more than that of Group B. Statistically significant improvement was observed in objective and subjective parameters in all 3 groups after completion of the course of treatment. The present study not only corrects the metabolic error by maintaining the Agni in equilibrium but also overcomes its various complications by stabilizing the status of Ojas in NIDDM patients.